Varieties of Human Capital, Growth and Productive Investment: what Supply Policy for France - Landais , Bernard (Studia Oeconomica Posnaniensia, 2026)
This paper considers the concerns about slow economic growth in Europe and especially in France. With the help of a neoclassical type model, it emphasizes the role played by productive investment and its main determinants, profit being in the first rank. Coming from the idea that one of the more important forms of human capital is the aptitude to assess and to cope with risk, it may be said that this aptitude is fundamental for elevating the growth potential in the long run. To avoid stagnation, tax policies aiming to increase net profits and savings may be quickly undertaken. Both mentalities and institutions must be modified by supply policies intended to increase the particular sort of human capital used to promote productive investment. These joint reforms would permit a boost in the investment rates, the growth potential and the standard of living in the long run.